Dissociation of chitosomes by digitonin into 16 S subunits with chitin synthetase activity - Ruiz-Herrera, J.; Bartnicki-Garcia, S.; Bracker, C.E. (Biochimica et biophysica acta, 1980)
Digitonin exerts profound effects on chitosomes (microvesicular structures with chitin synthetase activity isolated from the fungus Mucor rouxii). At low concentrations, it stimulates chitin synthetase (UDP-2-acetamido-2-deoxy- D-glucose : chitin 4-β-acetamidodeoxy- D-glucosyltransferase, EC 2.4.1.16) activity; at higher concentrations, it inhibits it. Digitonin also causes disintegration of the chitosome and the release of a homogeneous population of chitosome subunits with chitin synthetase activity. These chitosome subunits have a sedimentation coefficient of 16 S, compared to 105 S for whole chitosomes, as determined by centrifugation in sucrose density gradients, and measure 7–12 nm in diameter. After dissociation, chitin synthetase remains in a zymogenic state, and requires treatment with a protease for activation. No change in sedimentation coefficient of chitosome subunits was observed after proteolytic activation. The product synthesized by the chitosome subunits was characterized by X-ray diffractometry as α-chitin and was by this criterion indistinguishable from chitin made by preparations of undissociated chitosomes. However, in the electron microscope, the chitin microfibrils made from chitosome subunits were, in general, much shorter than those produced by undissociated chitosomes and often exhibited a needle-like appearance.